2022
DOI: 10.3390/ijerph19138097
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Family Caregivers’ Readiness for the Hospital Discharge of Advanced Cancer Patients

Abstract: Background: Many family caregivers of advanced cancer patients worry about being unable to provide in-home care and delay the discharge. Little is known about the influencing factors of discharge readiness. Methods: This study aimed to investigate the influencing factors of family caregivers’ readiness, used a cross-sectional survey, and enrolled 123 sets of advanced cancer patients and family caregivers using convenience sampling from four oncology wards in a medical centre in northern Taiwan. A self-develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…However, the level of discharge preparedness can vary based on the nurse’s experience and background. A previous study identified factors associated with caregivers’ discharge readiness, such as the patient’s physical activity and discharge preparation, the presence of someone to help, and the difficulty of care (Huang et al, 2022 ). Similar findings were observed in another study, highlighting factors such as patient functional status, disease and symptom status, connections to community resources/support, home safety needs, and environmental and care coordination influencing caregiver discharge readiness (OConnor et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of discharge preparedness can vary based on the nurse’s experience and background. A previous study identified factors associated with caregivers’ discharge readiness, such as the patient’s physical activity and discharge preparation, the presence of someone to help, and the difficulty of care (Huang et al, 2022 ). Similar findings were observed in another study, highlighting factors such as patient functional status, disease and symptom status, connections to community resources/support, home safety needs, and environmental and care coordination influencing caregiver discharge readiness (OConnor et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty can markedly affect caregivers' quality of life. [6][7][8][9] The coping style of family caregivers is multifaceted, influencing their response to the challenges they face. Their coping strategies may include problem-solving, seeking social support, positive reframing, and acceptance, among others.…”
Section: Introductionmentioning
confidence: 99%